Growing season evapotranspiration in boreal fens in the Athabasca Oil Sands Region: Variability and environmental controls. Issue 2 (5th January 2021) - Volik, Olena; Kessel, Eric; Green, Adam; Petrone, Richard; Price, Jonathan
Abstract: Current efforts to assess changes to the wetland hydrology caused by growing anthropogenic pressures in the Athabasca Oil Sands Region (AOSR) require well‐founded spatial and temporal estimates of actual evapotranspiration (ET), which is the dominant component of the water budget in this region. This study assessed growing season (May–September) and peak growing season (July) ET variability at a treed moderate‐rich fen and treed poor fen (in 2013–2018), open poor fen (in 2011–2014), and saline fen (in 2015–2018) using eddy covariance technique and a set of complementary environmental data. Seasonal fluctuations in ET were positively related to net radiation, air temperature and vapour pressure deficit and followed trends typical for the Boreal Plains (BP) and AOSR with highest rates in June–July. However, no strong effect of water table position on ET was found. Strong surface control on ET is evident from lower ET values than potential evapotranspiration (PET); the lowest ET/PET was observed at saline fen, followed by open fen, moderately treed fen, and heavily treed fen, suggesting a strong influence of vegetation on water loss. In most years PET exceeded precipitation (P), and positive relations between P/PET and ET were observed with the highest July ET rates occurring under P/PET 1. However, during months with P/PET > 1, increased P/PET was associated with decreased July ET. With respect to 30‐year mean values of air temperature and P in the area, both dry and wet, cool and warm growing seasons (GS) were observed. No clear trends between ET values and GS wetness/coldness were found, but all wet GS were characterized by peak growing seasons with high daily ET variability. Abstract : Multiyear evapotranspiration (ET) and potential evapotranspiration (PET) at four boreal fens are estimated, and the effect of net radiation (Rnet), air temperature (Tair), water table depth (WTD), and vapour pressure deficit (VPD) on ET is analyzed.